The Impact of Air Quality on the Distribution of Bronchial Asthma - Erdene-Ochir , Enkhmaa (Mongolian Journal of Strategic Studies, 2025)
In the structure of population morbidity in Mongolia, diseases of the respiratory system consistently rank first. This is not only associated to the country’s harsh climate but also significantly influensed by the air pollution in urban areas. The widespread occurrence of Bronchial asthma, especially in the recent years, has been the main motivation for this study. According to the result of the study, over the past decade, the distribution of Bronchial asthma among the population of Ulaanbaatar is 1.1 times higher than that of the 21 provinces, and the incidence has continued to grow annually. Research findings show that various airborne substances affect the disease differently. In particular, the current level of sulfur dioxide (SO2) and nitrogen dioxide (NO2) in the air have a strong influence on the development of Bronchial asthma, whereas PM10 and PM2.5 particles appear to have minimal or no significant impact. Гуурсан хоолойн багтраа өвчний тархалтад агаарын чанар нөлөөлөх нь Хураангуй: Монгол Улсын хүн амд Амьсгалын эрхтэн тогтолцооны эмгэг, ялангуяа Гуурсан хоолойн багтраа өвчний тархалт сүүлийн жилүүдэд түгээмэл болсон нь энэхүү судалгааг хийх үндэслэл болсон юм. Судалгааны үр дүнгээс үзвэл сүүлийн арван жилд Гуурсан хоолойн багтраа өвчний тархалт Улаанбаатар хотын хүн амд 21 аймгийнхаас 1.1 дахин их байгаа бөгөөд өвчлөл жилээс жилд эрс ихсэж байна. Энэ өвчинд агаарын найрлага дахь бодисууд харилцан адилгүй нөлөөлдөг нь судалгааны үр дүнгээс харагдлаа. Ялангуяа хүхэрлэг хий (SO2), азотын давхар исэл (NO2)-ийн агаар дахь агууламжийн өнөөгийн түвшин Гуурсан хоолойн багтраа үүсэхэд маш хүчтэй нөлөөлж байгаа бол PM10, PM2.5 тоосонцрууд үндсэндээ холбогдолгүй байна. Түлхүүр үг: Агаарын бохирдол, гуурсан хоолойн багтраа, хүхэрлэг хий, азотын давхар исэл, нүүрстөрөгчийн дутуу исэл